Systematic Literature Review: Teachers' Educational Interaction with Students in Learning in Indonesia - Ribut Wahyu Eriyanti; Ainur Rofiq; Atok Miftahul Huda; Endang Sri Estimurti (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Background: Educative interaction between teachers and students in learning is a definite thing, and if it is not carried out well, it will trigger learning problems at school. Research on educational interactions is trending and has become an important study in education. This research aims to analyze the educational interactions of teachers and students in learning at school. Method :This research uses the SLR (Systematic Literature Review) method. Data was collected by documenting and reviewing previous articles related to interaction and education. Article searches were carried out by searching for articles using the Scopus database. The subjects studied in this research are education, social interaction, interpersonal communication, human relations, interaction, interpersonal relations, students, and teaching. The initial database was 113,234, and then the researchers re-specified it so that it was found to be 475 documents. Results and Dıscussion: The research results show that articles dominate discussions about educational interactions, and there is still very little study of reviews, book chapters, and letters. Social sciences, health, and computer science dominate the subject of discussion. National institutions, especially in the health sector, are more dominant in funding studies on educational interactions. From the Scopus database obtained, publications about educational interactions in learning are still very rare